ANTIBIOGRAM OF TRACHYSPERMUM AMMI (AJWAIN) AGAINST TEST MICROORGANISMS - Atika Liaqat; Faqeer Hussain Khan; Liaqat Ali et al. (Journal of University Medical & Dental College, 2017)
Abstract: Statement of problem In the existing scenario, where the continuous rise in emergence of multi resistance pathogens is posing serious health threats, there is an urgent need to find out other (preferably natural) sources for safe and effective therapeutic agents as alternative to antibiotics. Objectives: The main objective is to find out and evaluate the antimicrobial potential of trachyspermun ammi against two most problematic pathogens (gram +ve S.aureous and gram –ve S.typhi) Study design: Experimental / in vitro study conducted in department of School of pharmacy, The University of-Faisalabad during September 2015 to February 2016. Methodology: Antimicrobial activity of crude extract of trachyspermun ammi was evaluated by standard Disc Diffusion Method and compered with standard antibiotic (ciprofloxacin). Results: Crude extract of trachyspermun ammi manifested remarkable antibiotic activity (30.33±0.33mm) against test organisms even surpassing the activity of control antibiotic (29.17±0.17mm). Statistical analysis: Investigated plant extract revealed significant antibacterial activity, which was significantly more /greater than the reference drug. Conclusion: Study finding indicate the presence of highly potent broad spectrum antimicrobial compounds/agents in the plant under investigation (trachyspermun ammi).